The effects of exercise training and nutritional supplementation on taekwondo performance: a systematic review and meta-analysis - Xu, Chen; Zhang, Wenxin; Luo, Lin (Frontiers in Nutrition, 2025)
BackgroundTaekwondo involves dynamic kicking and intermittent high-intensity efforts; the quantitative effects of training and supplementation on sport-specific outcomes remain unclear.ObjectiveTo systematically quantify the effects of exercise training and nutritional supplementation on taekwondo-specific performance indicators—TSAT, FSKT (10-s and multiple-bout), CMJ, VO2max, and heart-rate indices (HRmean, HRmax, HRpeak)—and to explore potential moderators.MethodsA PRISMA-guided systematic review and random-effects meta-analysis (SMD, 95% CI) were conducted on randomized or quasi-experimental studies involving taekwondo athletes. Risk of bias was assessed using RoB 2.0. Primary outcomes included TSAT and FSKT performance; secondary outcomes included CMJ, VO2max, and HR indices.ResultsExercise training significantly improved TSAT (SMD = −0.82; 95% CI: −1.43 to −0.21), FSKT-10s (SMD = 0.82; 95% CI: 0.15–1.49), FSKT-mult (SMD = 0.95; 95% CI: 0.55–1.35), and VO2max (SMD = 1.54; 95% CI: 0.58–2.49); CMJ (SMD = 0.21; 95% CI: −0.02–0.45) and HRmax (SMD = −0.02; 95% CI: −0.48–0.44) showed no significant changes. Nutritional supplementation—especially caffeine—improved TSAT (SMD = −1.41; 95% CI: −2.24 to −0.57), FSKT-10s (SMD = 1.82; 95% CI: 1.08–2.57), FSKT-mult (SMD = 1.67; 95% CI: 0.72–2.62), and VO2max (SMD = 0.95; 95% CI: 0.60–1.31), with no effect on HR_mean (SMD = 0.10; 95% CI: −0.28–0.47) or HRpeak (SMD = 0.28; 95% CI: −0.46–1.02).ConclusionBoth exercise training and nutritional supplementation significantly improve agility, repeated-kick performance, and aerobic capacity in taekwondo athletes. Nevertheless, the findings should be generalized cautiously due to the observed heterogeneity. Future well-designed, adequately powered randomized controlled trials with standardized protocols are warranted.Systematic review registrationIdentifier: CRD420251007058.